Zyflamend, a unique herbal blend, induces cell death and inhibits adipogenesis through the coordinated regulation of PKA and JNK. (1st January 2020) - Puckett, Dexter; Alquraishi, Mohammed; Alani, Dina S.; Chahed, Samah; Frankel, Victoria D.; Donohoe, Dallas; Voy, Brynn; Whelan, Jay; Bettaieb, Ahmed
ABSTRACT: The prevalence of obesity and its comorbidities has sparked a worldwide concern to address rates of adipose tissue accrual. Recent studies have demonstrated a novel role of Zyflamend, a blend of natural herbal extracts, in regulating lipid metabolism in several cancer cell lines through the activation of the AMPK signalling pathway. Yet, the role of Zyflamend in adipogenic differentiation and lipid metabolism remains largely unexplored. The objective of this study is to investigate the effects of Zyflamend on white 3T3-MBX pre-adipocyte differentiation and elucidate the molecular mechanisms. We demonstrate that Zyflamend treatment altered cell cycle progression, attenuated proliferation, and increased cell death of 3T3-MBX pre-adipocytes. In addition, treatment with Zyflamend inhibited lipid accumulation during the differentiation of 3T3-MBX cells, consistent with decreased expression of lipogenic genes and increased lipolysis. Mechanistically, Zyflamend-induced alterations in adipogenesis were mediated, at least in part, through the activation of AMPK, PKA, and JNK. Inhibition of AMPK partially reversed Zyflamend-induced inhibition of differentiation, whereas the inhibition of either JNK or PKA fully restored adipocyte differentiation and decreased lipolysis. Taken together, the present study demonstrates that Zyflamend, as a novel anti-adipogenic bioactive mix, inhibits adipocyte differentiation through the activation of the PKA and JNK pathways. Abbreviation : 7-AAD: 7-amino-actinomycin D; ACC: acetyl-CoA carboxylase; AKT: protein kinase B; AMPK: AMP-activated protein kinase; ATGL: adipose triglyceride lipase; C/EBPα: CCAAT-enhancer binding protein alpha; DMEM: Dulbecco's Modified Eagle Medium; DMSO: dimethyl sulphoxide; DTT: dithiothreitol; EGTA: ethylene glycol-bis-(2-aminoethyl)-N, N, N', N'-tetraacetic acid; ERK: extracellular signal–regulated kinases; FASN: fatty acid synthase; FBS: foetal bovine serum; GLUT: glucose transporter; HSL: hormone-sensitive lipase; IR: insulin receptor; IRS: insulin receptor substrate; JNK: c-JUN N-terminal kinase; MGL: monoacylglycerol lipase; NaF: sodium fluoride; NF-κB: nuclear factor kappa-light-chain-enhancer of activated B cells; PBS: phosphate buffered- saline; PCB: pyruvate carboxylase; PDE: phosphodiesterase; PKA: protein kinase cAMP-dependent; PMSF: phenylmethylsulfonyl fluoride; PPARγ: perilipin peroxisome proliferator-activated receptor gamma; PREF-1: pre-adipocyte factor 1; PVDF: polyvinylidene fluoride; RIPA: radio-immunoprecipitation assay; SDS-PAGE: sodium dodecyl sulphate polyacrylamide gel electrophoresis; SEM: standard error of the mean; SOX9: suppressor of cytokine signalling 9; TGs: triacylglycerols.